2020
DOI: 10.1029/2019gl085637
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of the Pitch Angle Scattering of Relativistic Electrons Induced by EMIC Waves

Abstract: In this study, we analyze an electromagnetic ion cyclotron (EMIC) wave event of rising tone elements recorded by the Van Allen Probes. The pitch angle distributions of relativistic electrons exhibit a direct response to the two elements of EMIC waves: at the intermediate pitch angle, the fluxes are lower; and at the low pitch angle, the fluxes are higher than those when no EMIC was observed. In particular, the observed changes in the pitch angle distributions are most likely to be caused by nonlinear wave‐part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 60 publications
5
32
0
Order By: Relevance
“…These can also be seen at 1.8 and 2.6/3.4 MeV (not shown), but the signal as measured by REPT gets very weak at energies beyond this. Similar signatures were observed by Zhu et al (2020) and shown to be a result of nonlinear interaction between rising tone EMIC waves and MeV electrons, which can scatter particles toward the loss cone via phase trapping. Kurita et al (2018) also observed scattering of lower pitch angle MeV electrons in association with EMIC wave activity.…”
Section: Magnetospheric Responsesupporting
confidence: 72%
“…These can also be seen at 1.8 and 2.6/3.4 MeV (not shown), but the signal as measured by REPT gets very weak at energies beyond this. Similar signatures were observed by Zhu et al (2020) and shown to be a result of nonlinear interaction between rising tone EMIC waves and MeV electrons, which can scatter particles toward the loss cone via phase trapping. Kurita et al (2018) also observed scattering of lower pitch angle MeV electrons in association with EMIC wave activity.…”
Section: Magnetospheric Responsesupporting
confidence: 72%
“…The analysis showed that electron precipitation occurred at energies at least down to ∼200-300 keV, potentially associated with EMIC waves, indicating that when EMIC waves are efficient in pitch angle scattering, they likely precipitate lower energy electrons together with the expected ∼MeV ones. The nature of the wave-particle interaction at such low energies cannot be explained with the traditional quasi-linear theory (Capannolo et al, 2019b) and is currently under active research (e.g., Blum et al, 2019;Chen et al, 2016;Denton et al, 2019;Hendry et al, 2019;Nakamura et al, 2019;Wang et al, 2018;Zhu et al, 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…From previous studies, EMIC waves can scatter relativistic electrons (e.g., Blum et al., 2015; Cao et al., 2017; Miyoshi et al., 2008; Ni et al., 2015; Omura & Zhao, 2013; Rodger et al., 2015; Su et al., 2017; Usanova et al., 2014; Z. Wang et al., 2014; Wang, Su, et al., 2017; X. J. Zhang et al., 2016; Zhu et al., 2020, and others), lead to the decay of ring current ions (Daglis et al., 1999; Fuselier et al., 2004; Su et al., 2014), or heat the cold electrons (Thorne et al., 2006; Yuan et al., 2014). The present study clearly demonstrates the existence of unguided mode EMIC waves in the radiation belt, and propose a trapping and amplification mechanism for explaining their origin.…”
Section: Discussionmentioning
confidence: 99%
“…The earth radiation belt is dynamically influenced by multiple types of waves, one of them is the electromagnetic ion cyclotron (EMIC) wave, which has been widely investigated in recent decades [1][2][3][4][5][6][7][8][9] , and has been considered to have the potential to remove the relativistic electrons from the radiation belt over a time-scale of several hours [10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%